YouTube and food allergy: An appraisal of the educational quality of information. Issue 4 (15th April 2018) - Reddy, Keerthi; Kearns, Mary; Alvarez‐Arango, Santiago; Carrillo‐Martin, Ismael; Cuervo‐Pardo, Nathaly; Cuervo‐Pardo, Lyda; Dimov, Ves; Lang, David M.; Lopez‐Alvarez, Sonia; Schroer, Brian; Mohan, Kaushik; Dula, Mark; et al.
Abstract: Background: Food allergy affects an estimated 8% of children and 3% of adults in the United States. Food‐allergic individuals increasingly use the web for medical information. We sought to determine the educational quality of food allergy YouTube videos. Methods: We performed a YouTube search using keywords "food allergy" and "food allergies". The 300 most viewed videos were included and analyzed for characteristics, source, and content. Source was further classified as healthcare provider, alternative medicine provider, patient, company, media, and professional society. A scoring system (FA‐DQS) was created to evaluate quality (−10 to +34 points). Negative points were assigned for misleading information. Eight reviewers scored each video independently. Results: Three hundred videos were analyzed, with a median of 6351.50 views, 19 likes, and 1 dislike. More video presenters were female (54.3%). The most common type of video source was alternative medicine provider (26.3%). Alternative treatments included the following: water fast, juicing, Ayurveda, apple cider, yoga, visualization, and sea moss. Controversial diagnostics included kinesiology, IgG testing, and pulse test. Almost half of the videos depicted a non‐IgE‐mediated reaction (49.0%).Videos by professional societies had the highest FA‐DQS (7.27). Scores for videos by professional societies were significantly different from other sources ( P < .001). There was a high degree of agreement among reviewers (ICC = 0.820; P < .001). Conclusion: YouTube videos on food allergy frequently recommend controversial diagnostics and commonly depict non‐IgE‐mediated reactions. There is a need for high‐quality, evidence‐based, educational videos on food allergy.